2018
DOI: 10.1007/s40199-018-0218-0
|View full text |Cite
|
Sign up to set email alerts
|

A simulation model to evaluate pharmaceutical supply chain costs in hospitals: the case of a Colombian hospital

Abstract: Background Healthcare costs is one of the most studied issue in our days because of increasing demand and the aging of population. Final costs of medicines is one of the most important issue in patient treatment and determine its real value is an important task within hospitals. Simulation models and in this case system dynamics allows to build representations of reality considering the interaction of the whole variables that affect the system where first a causal loop diagram allows to represent and identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…A previous study suggested to speed-up the process of COVID-19 vaccine development, the time of clinical phases II and III can be reduced by using human challenge studies through deliberate infection of healthy volunteers with the virus after administration of the tested vaccine. 25 , 26 This might increase the fear of volunteers and thus the willingness to participate in the clinical trials, as shown by the current study findings. However, speeding the development of the vaccine for the purpose of saving human lives could be ethically justified.…”
Section: Discussionmentioning
confidence: 62%
“…A previous study suggested to speed-up the process of COVID-19 vaccine development, the time of clinical phases II and III can be reduced by using human challenge studies through deliberate infection of healthy volunteers with the virus after administration of the tested vaccine. 25 , 26 This might increase the fear of volunteers and thus the willingness to participate in the clinical trials, as shown by the current study findings. However, speeding the development of the vaccine for the purpose of saving human lives could be ethically justified.…”
Section: Discussionmentioning
confidence: 62%
“…[ 29 ] Instead, the research has shifted to COVID-19 investigations into finding a curative treatment are granted and facilitated by national and international research bodies, while we observe dysregulation and anarchy or probably pseudo-research in clinical studies and clinical use of drugs as off-label usage, compassionate use or clinical practice. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Papalexi et al (2015) focused on the implementation of the kanban system on the supply chain for a group of cooperative pharmacists proposing that the organisation can store 56.8% fewer products and spend 71.8% less money, by adopting the kanban system. Simulation modelling and outsourcing of noncritical medical supplies were examined by scholars such as Battini et al (2013) and Franco (2018), aiming at reducing inventory costs without influencing the quality of services. Danese (2006) suggested the use of Information Technology (IT) across the network for sharing and exchanging information and highlighted the significance of trust within it.…”
Section: Innovation In the Pscmentioning
confidence: 99%
“…Although they found that the application of Computerised Provider Order Entry (CPOE), Electronic Medical Record (EMR) and other similar software for placing pharmaceutical orders electronically has multiple benefits, the cost of implementing those types of technology were one of the limitations (Shafique et al, 2019). In addition, Davenport (2013) and Franco (2018), who also focused on the financial aspects of innovation, suggested that organisations often hesitate to undertake an innovative approach, fearing the economic risk associated with this type of initiative specifically when attempts to be innovative fail. Considering that the cost of pharmaceuticals is too high (Cherrett et al, 2012), pharmacies do not consider that purchasing and maintaining this type of technology requires huge investments.…”
Section: Factors Influencing the Level Of Innovation Within The Downstream Domain Of The Pharmaceutical Supply Chainmentioning
confidence: 99%